Fatal idiopathic giant cell myocarditis in a young male: a diagnostic and therapeutic dilemma in a resource-limited setting - N. M. M. Risly; I. K. Jayasinghe; N. Athauda; V. D. Wijekoon; P. D. Fonseka; J. F. Sahana (Asian Journal of Internal Medicine)
Idiopathic giant cell myocarditis (IGCM) is a rare and rapidly progressive form of myocarditis characterised by severe myocardial inflammation, rapid deterioration and high mortality without timely intervention. We report a fatal case of a 15-year-old boy who presented with worsening dyspnoea and signs of congestive cardiac failure which rapidly progressed to cardiogenic shock. Extensive investigations including imaging, biopsies, viral and autoimmune panels excluded other potential aetiologies such as infiltrative cardiomyopathies, cardiac sarcoidosis, lymphocytic myocarditis and lymphomas. Due to the unavailability of confirmatory endomyocardial biopsy, a clinical diagnosis of IGCM was made, and immunosuppressive therapy was initiated. Despite aggressive management, the patient succumbed to the disease due to refractory heart failure and fatal arrhythmia. This case highlights the diagnostic and therapeutic challenges of IGCM, particularly in resource-limited settings, and the importance of considering IGCM in cases of fulminant myocarditis with rapid progression. Early diagnosis and advanced modalities of treatment are crucial to improve outcomes in this life-threatening condition.